2018
DOI: 10.26717/bjstr.2018.03.000910
|View full text |Cite
|
Sign up to set email alerts
|

Major Compounds from Ocimum Basilicum l. and their Antimicrobial Activity against Methicillin-Resistant Staphylococcus Aureus

Abstract: Sweet Basil (Ocimum basilicum Linn.) has a variety of therapeutic properties, including antimicrobial activity. This study aimed to determine the antibacterial activity of the major chemical components in the crude extract against methicillin resistant Staphylococcus aureus (MRSA) isolated from the clinical specimens. TLC and column chromatography resulted in the separation of two major compounds. On the basis of the spectral data, they were identified as linalool (1) and 1,8-cineole (2). Antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The antimicrobial properties of basil have been demonstrated in various studies [50,76]. Taecowisan et al [77] indicated that the basil's antibacterial effect is related to the major components of basil extract, namely linalool and 1,8-cineol. Many studies have also shown the stimulatory effects of various herbal medicines, including Lawsonia inermis [78], oregano herb [74], and Artemisia Drncuculus [30], in boosting the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial properties of basil have been demonstrated in various studies [50,76]. Taecowisan et al [77] indicated that the basil's antibacterial effect is related to the major components of basil extract, namely linalool and 1,8-cineol. Many studies have also shown the stimulatory effects of various herbal medicines, including Lawsonia inermis [78], oregano herb [74], and Artemisia Drncuculus [30], in boosting the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Taechowisan et al, Ocimum basilicum Linn. crude extract is an active agent against methicillin-resistant Staphylococcus aureus (MRSA) [ 52 ]. Using the diffusion method, the researchers determined the very high microbial activity of the crude extract at 34.5 mg/disc.…”
Section: Natural Compounds With Antimicrobial Properties As Cosmetic ...mentioning
confidence: 99%
“…Using the diffusion method, the researchers determined the very high microbial activity of the crude extract at 34.5 mg/disc. Moreover, they noticed that the crude extract and the main isolated compound linalool showed higher activity against MRSA with MIC < 0.09 mg/mL and MBC ≤ 0.09 to 0.38 mg/mL than 1,8-cineole [ 52 ]. Kaya et al conducted research on basil extracts obtained using various extractants: chloroform, acetone, and methanol (in two different water resuspension doses of 5 and 10 mL).…”
Section: Natural Compounds With Antimicrobial Properties As Cosmetic ...mentioning
confidence: 99%
“…The recent research has shown that the essential oil of Ocimum basilicum has an inhibiting action on certain fungi such as Rhizoctonia, Macrophomina phaseolina, Aspergillus niger, Aspergillus fumigates, Aspergillus flavus, Candida albicans and Penicillium [37,38]. Thongchai et al carried out a thorough study on the leaf extracts of Ocimum basilicum [39]. They have been investigated against Methicillin-resistant Staphylococcus aureus (MRSA) isolated from clinical samples.…”
Section: Ocimum Basilicummentioning
confidence: 99%